Chemokine-mediated recruitment of NK cells is a critical host defense mechanism in invasive aspergillosis - Morrison, Brad E. (American Society for Clinical Investigation, 2003)
Invasive aspergillosis is a severe pneumonia that is usually fatal despite currently available therapy. The disease disproportionately afflicts immunocompromised patients, indicating the critical importance of the immune status of the host in this infection, but the defense mechanisms against this pathogen remain incompletely understood. In the current study, we hypothesized that the chemokine ligand monocyte chemotactic protein-1, also designated CC chemokine ligand-2 (MCP-1/CCL2) is necessary for effective host defense against invasive aspergillosis in immunocompromised hosts. We found a rapid and marked induction of MCP-1/CCL2 in the lungs of neutropenic mice with invasive aspergillosis. Neutralizing MCP-1/CCL2 resulted in twofold greater mortality and greater than threefold increase in pathogen burden in the lungs. Neutralization of MCP-1/CCL2 also resulted in reduced recruitment of NK cells to the lungs at early time points, but did not affect the number of other leukocyte effector cells in the lungs. Ab-mediated depletion of NK cells similarly resulted in impaired defenses against the infection, resulting in a greater than twofold increase in mortality and impaired clearance of the pathogen from the lungs. These data establish MCP-1/CCL2–mediated recruitment of NK cells to the lungs as a critical early host defense mechanism in invasive aspergillosis and demonstrate NK cells to be an important and previously unrecognized effector cell in this infection.